A dramatistic analysis of Indonesian influencers' statements in responding to sexual harassment allegations - Tendean, Meriell Jade E. (International Journal of Communication and Society, 2022)
This article aims to dig deeper and reveal the rhetorical strategies of three influencers who are alleged sexual harassment perpetrators in their statements on social media. Social media has given a way for sexual harassment victims to expose their perpetrators, including those who are public figures. However, the alleged perpetrators are also given the same platform to share their statements. Recently, there have been many sexual harassment allegations against social media influencers and celebrities. These public figures then used the same social media platforms they were already familiar with to publish their statements. The study uses qualitative assessment and observation on video statements from Indonesian influencers, Billy Joe Ava, Gofar Hilman, and Niko Al Hakim. Analyses were made based on Kenneth Burke’s Dramatism theory, defining the pentadic elements, and assessing the guilt and redemption approach, as well as the identification strategy. Findings from the assessment reveal that in addressing the allegations, two pentadic elements are dominantly used, agent and scene, with the aim of identifying themselves with the audience, providing a background of the accusation, and hence maintaining influence on their audience. Moreover, scapegoating is the main redemption strategy, with variations in the chosen scapegoats.